Implementation of Character Education Based on the Exemplary Model of Prophet Muhammad in Early Childhood Education - Ema Nurmawati; Amat Hidayat; Yolanda Pahrul (UNIB Press, 2026)
Early childhood education is crucial in molding children's personalities during their formative years. The purpose of this study is to assess how the prophet-based educational approach is applied in early childhood education and to look at how parents and teachers support their children's character development. A case study design and a descriptive qualitative methodology were used in this investigation. Current parents, parents of alumni, teachers in the classroom, and the school administration were all chosen through the use of purposeful sampling. Data was gathered through thorough interviews, participatory observation, and documentation. The Miles and Huberman interactive model was used for data reduction, data display, and making conclusions. The results show that daily habituation, teacher role modeling, and parent-school cooperation were used to implement character education. Alumni parents' engagement shows that the moral principles taught in early childhood education are still relevant when kids depart from preschool.